Descriptive study of nursing scope of practice in rural medically underserved areas of Africa, South of the Sahara. (2017) - Msuya, Marycelina; Blood-Siegfried, Jane; Chugulu, Juliet; Kidayi, Paulo; Sumaye, John; Machange, Rogathe; Mtuya, Christina Chuki; Pereira, Katherine
Abstract: Aims: The aims of this study are to describe the scope of "non-nursing duties" carried out by nurses, in rural low-resource regions of Tanzania, and describe how the role of nurses is viewed in their communities. Background: More than 70% of Tanzanians live in rural areas. Nurses are more likely than physicians to practice in these communities. As a result nurses are frequently forced to function beyond their educational preparation and expand their practice to meet the health needs of the community. Design: This exploratory study sampled two randomly selected district hospitals, with associated health centers and dispensaries (small village clinics), in each of the four target-regions (Tanga, Mtwara, Singida, and Shinyanga). Methods: In November 2014, members of the Faculty of Nursing at Kilimanjaro Christian Medical University–College (KCMUCo) in Moshi, Tanzania interviewed nurses, health facility managers, non-nurse health professionals, and health service consumers. Results/findings: Nurses at all levels of education, with or without additional training, are prescribing for patients and performing minor surgical procedures, well beyond their educational preparation. The consensus by all participants is that nurses should receive training in skills to provide primary care as a solution to the lack of providers. Conclusion: Strengthening health services by advancing the nurses' role is an innovative way to improve health care outcomes in Tanzania.